Claudin-11 in health and disease: implications for myelin disorders, hearing, and fertility - Gjervan, Sophia C.; Ozgoren, Oguz K.; Gow, Alexander; Stockler-Ipsiroglu, Sylvia; Pouladi, Mahmoud A. (Frontiers in Cellular Neuroscience, 2024)
Claudin-11 plays a critical role in multiple physiological processes, including myelination, auditory function, and spermatogenesis. Recently, stop-loss mutations in CLDN11 have been identified as a novel cause of hypomyelinating leukodystrophy (HLD22). Understanding the multifaceted roles of claudin-11 and its potential pathogenic mechanisms in HLD22 is crucial for devising targeted therapeutic strategies. This review outlines the biological roles of claudin-11 and the implications of claudin-11 loss in the context of the Cldn11 null mouse model. Additionally, HLD22 and proposed pathogenic mechanisms, such as endoplasmic reticulum stress, will be discussed.